Light quality regulates flowering in FvFT1/FvTFL1 dependent manner in the woodland strawberry Fragaria vesca - Rantanen, Marja; Kurokura, Takeshi; Mouhu, Katriina; Pinho, Paulo; Tetri, Eino; Halonen, Liisa; Palonen, Pauliina; Elomaa, Paula; Hytönen, Timo (Frontiers in Plant Science, 2014)
Control of flowering in the perennial model, the woodland strawberry (Fragaria vesca L.), involves distinct molecular mechanisms that result in contrasting photoperiodic flowering responses and growth cycles in different accessions. The F. vesca homolog of TERMINAL FLOWER1 (FvTFL1) functions as a key floral repressor that causes short-day (SD) requirement of flowering and seasonal flowering habit in the SD strawberry. In contrast, perpetual flowering F. vesca accessions lacking functional FvTFL1 show FLOWERING LOCUS T (FvFT1)-dependent early flowering specifically under long-days (LD). We show here that the end-of-day far-red (FR) and blue (B) light activate the expression of FvFT1 and the F. vesca homolog of SUPPRESSOR OF THE OVEREXPRESSION OF CONSTANS (FvSOC1) in both SD and LD strawberries, whereas low expression levels are detected in red (R) and SD treatments. By using transgenic lines, we demonstrate that FvFT1 advances flowering under FR and B treatments compared to R and SD treatments in the LD strawberry, and that FvSOC1 is specifically needed for the B light response. In the SD strawberry, flowering responses to these light quality treatments are reversed due to up-regulation of the floral repressor FvTFL1 in parallel with FvFT1 and FvSOC1. Our data highlights the central role of FvFT1 in the light quality dependent flower induction in the LD strawberry and demonstrates that FvTFL1 reverses not only photoperiodic requirements but also light quality effects on flower induction in the SD strawberry.